2022
DOI: 10.1039/d2dt01693a
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature luminescence from Pd(ii) and Pt(ii) complexes: from mechanochromic crystals to flexible polymer matrices

Abstract: A series of Pd(ii) and Pt(ii) complexes bearing tetradentate ligands as dianionic luminophores were synthesized and their room-temperature photoluminescence in PMMA films as well as in mechanochromic crystalline phases was correlated with molecular structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…However, in this case, the photophysical properties were not improved by aggregation in the same way as in the previous article. Complexes 81 and 82 were further studied later [ 90 ], both showing very poor emission in fluid solutions due to dissociative MC states thermally accessible at room temperature. At 77 K, in a frozen 1:1 DCM/MeOH glassy matrix, 79 – 82 show a blue-shift in the emission spectra when compared to data gathered at 298 K, as well as unitary Φ L values and a drastic increase in their lifetimes.…”
Section: Orthopalladated Ligandsmentioning
confidence: 99%
“…However, in this case, the photophysical properties were not improved by aggregation in the same way as in the previous article. Complexes 81 and 82 were further studied later [ 90 ], both showing very poor emission in fluid solutions due to dissociative MC states thermally accessible at room temperature. At 77 K, in a frozen 1:1 DCM/MeOH glassy matrix, 79 – 82 show a blue-shift in the emission spectra when compared to data gathered at 298 K, as well as unitary Φ L values and a drastic increase in their lifetimes.…”
Section: Orthopalladated Ligandsmentioning
confidence: 99%
“…The 3-n compounds were obtained as main products by working with 1.2 equivalents of the boronic acid. Based on our previous work, we took advantage of the free phenol moiety to provide diverse alkyl chain lengths employing a straightforward Williamson's ether synthesis, thus yielding compounds 4-n. [21] Finally, a second Suzuki-Miyaura cross-coupling reaction between 4-n and the selected boronic acid provided the intended asymmetric ligands L Fpy -n and L Ph -n (n = 6, 12, and 18). The Pt(II) complexes PtL Fpy -n and PtL Ph -n (n = 6, 12, and 18) were synthesized by well-established cycloplatination conditions employing the corresponding ligand and K 2 PtCl 4 in glacial acetic acid at 130 • C. Detailed experimental procedures, as well as the exact mass (EM) spectrometry data and 2D-NMR spectra including the unambiguous signal assignment for all ligand precursors and their complexes, can be found in the Supporting Information (Figures S1-S114).…”
Section: Synthesis Of the Complexesmentioning
confidence: 99%
“…[28][29][30] All the compounds have significantly higher Φ L at r.t. than previous Pt(II) complexes with tetradentate luminophores reported by our group (Figures S117-S134). [13,21,24] This outcome probably stems from the replacement of the orthogonal-to-plane phenyl ring on the bridging N-atom by a slim alkyl moiety; hence, it reduces the non-radiative deactivation of the excited state via molecular distortion caused by repulsion between the Hatoms of the phenyl group at the bridge and at the pyridine rings of the luminophore. [24] At 77 K, all the complexes have unitary Φ L within the experimental uncertainty, which can be ascribed to the inaccessible thermal population of dissociative metal-centered states (MC, which would provide radiationless deactivation channels by conical intersections with the ground state).…”
Section: Photophysical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthily, very few examples of Pd II complexes that showed RT aggregation-induced phosphorescent emission have been reported so far (Figures B and S18). ,, Strassert et al described Pd II complexes featuring tetradentate ligands, while Lu et al reported pincer Pd II allenylidene derivatives . Although the aforementioned reports support the role of self-assembly as an enabler of phosphorescence, the extent to which solid-state phosphorescence can be generated rationally upon chemical structure analysis is compulsive for further investigation.…”
mentioning
confidence: 99%